Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
x² + 4 = 0
- 4 - 4
x² = -4
x = 2i
x² - 6x + 7 = 0
x = -(-6) +/- √((-6)² - 4(1)(7))
2(1)
x = 6 +/- √(36 - 28)
2
x = 6 +/- √(8)
2
x = 6 +/- 2√(2)
2
x = 3 + √(2)
x = 3 + √(2) x = 3 - √(2)
- 4 - 4
x² = -4
x = 2i
x² - 6x + 7 = 0
x = -(-6) +/- √((-6)² - 4(1)(7))
2(1)
x = 6 +/- √(36 - 28)
2
x = 6 +/- √(8)
2
x = 6 +/- 2√(2)
2
x = 3 + √(2)
x = 3 + √(2) x = 3 - √(2)
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.